Comparing timing of other-initiation of repair: a multimodal approach - Pajo, Kati; Laakso, Minna (Frontiers in Communication, 2023)
When recipients of talk solve troubles of hearing or understanding during a conversation, they utilize other-initiation of repair (OIR), such as questions “what", "where", and "you mean x”. These utterances are typically produced with delayed timing. Multimodal, bodily features are also typically included. Although troubles in hearing and understanding are common, there have been few studies comparing the timing of OIR of normally hearing individuals to individuals with hearing impairment, especially from a multimodal perspective. The current study examined video-recordings of 14 dyads with normal hearing and with mild to severe degree of hearing impairment. The research focused on verbal OIR sequences (N=167) and adopted a multimodal approach. The research questions were presented as follows: (1) In relation to the trouble source turn, what is the timing of OIRs?; (2) What visual bodily resources does the recipient utilize during OIR sequences?; (3) Does the timing of OIRs and their visual bodily style of production differ between participants with normal hearing and different degrees of hearing impairment? Conversation analysis with ELAN software was utilized for qualitative and statistical inspection of the data. The results show that gaps preceding OIRs displayed variation and mean values for participants with normal hearing and mild-to-moderate hearing impairment were ∼700 ms and with severe hearing impairment ∼500 ms. In comparison to other participants in the data, participants with severely deteriorated hearing produced OIRs without delay and utilized more overt visual bodily actions. Especially, ∼200 ms mean gap for open OIRs with participants with severe hearing impairment indicated very fast turn-taking, occurring even in overlap with the trouble source turn. However, all participants took a longer time to initiate restricted OIRs than open OIRs. In terms of visual bodily actions, the results showed some fundamental differences. Participants with severe hearing impairment held their gaze at the speaker more intensively than other participants. Other visual bodily actions, such as, upper body lean forward, or changes in facial expressions, were found in all participant groups. However, their frequency, timing, and quality displayed variation.